The Oneiric Journey of the Death. About Zjawienie Emilki of Jan Paweł Woronicz - Szadkowska, Olga (Wzniosłość i makabra w literackich obrazach śmierci, 2014)
This article is considering the journey of the death in Woronicz’s book, Zjawienie Emilki. Work of JanPaweł Woronicz includes vision of death girl, who tells her dreaming sister a story about things she hasseen in heaven. This specific type of journey (after death) has it ancient provenience. This article is consideringPlato’s myth of Er and Dream of Scipio as a two texts which have huge influence on Woronicz’swork. Furthermore this article presents tradition of prophetic texts as Profecja Księdza Marka Karmelity.It shows that not only Polish tradition (called preromantic), but also Ancient literature got impact on18th century poetry.